Adolescents' views on celebrity worship: A Qualitative study - Ang, Chin Siang; Chan, Nee Nee * (Springer Verlag (Germany), 2016)
A phenomenological study was conducted to explore the experiences of celebrity worshipers in Malaysia in order to identify the factors motivating celebrity worship, the meanings and impact gained from the worship experience. A purposive sample of 15 adolescents who identified themselves as celebrity worshipers, were interviewed. Thematic analysis revealed that 3 major factors influenced participants to become celebrity worshipers: celebrity products, personal characteristics of the celebrity, and peer influence. Also, the themes that emerged that described participants’ perceived impact of celebrity worship included emotional impact, development of strong self-determination and cultural awareness, and the enhancement of personal and social relationships. Generally, adolescents did not think there was a negative impact of their worship experiences. The study has revealed insights into how celebrities play an important role by inspiring young generation in positive ways.